Effect of Different High-Palladium Metal-Ceramic Alloys on the Color of Opaque Porcelain - Minos M. Stavridakis, DDS, MS,1 Efstratios Papazoglou, DDS, MS, PhD,2 (Blackwell Synergy, 2000)
The purpose of this study was to assess the effect of different high-palladium alloys on the resulting color of opaque porcelain. Three Pd-Cu-Ga alloys, Spartan Plus (S; Williams Dental Co/Division of Ivoclar North America, Amhest, NY), Liberty (B; J.F. Jelenko & Co, Armonk, NY), and Freedom Plus (F; J.F. Jelenko & Co); 4 Pd-Ga alloys, Legacy (L; J.F. Jelenko & Co), IS 85 (I; Williams Dental Co), Protocol (P;Williams Dental Co), and Legacy XT (X; J.F. Jelenko & Co); and a Pd-Ag alloy, Super Star (T; J.F. Jelenko & Co), were examined. The Au-Pd alloy Olympia (O; J.F. Jelenko & Co) served as the control.